The Control Right of Palm Oil Natural Resource and Its Impact on Society and the Environment. - Peilouw, Johanis Steny Franco (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Natural resources play a very important role in the survival of mankind. The fact is that the availability of natural resources is not evenly distributed in all countries in the world and this cannot be denied. Oil palm plantations are one of the productive natural resources that is very promising in the market sphere, but in their management there are still many deviations from the values of Pancasila and their implications for the environment. purposes of the research is to determine the impact of oil palm plantations on the environment. This research uses an empirical legal research method, namely a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The results of the research show that the regulation of control rights over natural resources in oil palm plantations is not based on the values of justice contained in Pancasila because there are no sanctions or supervision carried out on the Company so that in its implementation the Company does not carry out its responsibility to fulfill its obligations as it should. can improve the welfare of the people who entrust their country's land to be leased and used as oil palm plantations. The implications for society and the environment if it is not managed based on the values of justice are that the welfare of the community is not met which results in increased poverty and impacts on the environment where water pollution and drought occur due to oil palm planting.